International trade, hedging and the demand for forward contracts - Jens Eisenschmidt; Klaus Wälde (Technische Universität Dresden, Fakultät Wirtschaftswissenschaften, 2003)
There is a huge literature on the effects of uncertainty on trade levels. One very strong result of that literature is that uncertainty should not matter, as long as well developed forward markets exist. The empirical implications of this result, however, are hard to find in the data. We model terms of trade uncertainty in a small open economy with uncertainty stemming from abroad and derive the equilibrium demand for forward contracts. It turns out that risk averse agents will not buy forwards at an actuarially fair price, thus rendering both the full-hedge theorem and the separation theorem of the aforementioned literature obsolete. Using real world data for Germany we calibrate our model. We find that in equilibrium risk averse agents will buy forward cover only for nvestment reasons. The amount of forwards purchased is around 20% of equilibrium imports. This is broadly in accordance with empirical observed ratios.
Keywords: F00; F30; G10; 330; forward contracts; terms of trade uncertainty; hedging